(untitled) (Third Sector Social Economic Review, 2014)
Despite the decline in agricultural employment, agriculture, being the main economic activity at the rural country. While the size of Agriculture is decreasing proportionally within the national economy, agricultural foreign trade growth observed in the agricultural sector, shows that it has a dynamic market. In the European Union, there are serious activities of cooperatives/producer organizations at many agricultural markets. ""Promotion of Agricultural Products"" program is very important.Turkey has to benefit these kind of programmes. This paper tries to research and evaluate these policies and implementing possibilities in Turkey. If Turkey implements EU like policies, the share of cooperatives at global agricultural markets can be increased. This paper tries to help to this aim. Research/evaluation method was used.